A Quadratic Triangular Finite Volume Element Method for a Semilinear Elliptic Equation (Advances in Applied Mathematics and Mechanics, 2018)
In this paper we extend the idea of interpolated coefficients for a semilinearproblem to the quadratic triangular finite volume element method. At first, we introducequadratic triangular finite volume element method with interpolated coefficientsfor a boundary value problem of semilinear elliptic equation. Next, we derive convergenceestimate in $H^1$-norm, $L^2$-norm and $L^∞$-norm, respectively. Finally, an example isgiven to illustrate the effectiveness of the proposed method.